2013
DOI: 10.1016/j.neuron.2013.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Odor Discrimination Requires Proper Olfactory Fast Oscillations in Awake Mice

Abstract: Gamma oscillations are commonly observed in sensory brain structures, notably in the olfactory bulb. The mechanism by which gamma is generated in the awake rodent and its functional significance are still unclear. We combined pharmacological and genetic approaches in the awake mouse olfactory bulb to show that gamma oscillations required the synaptic interplay between excitatory output neurons and inhibitory interneurons. Gamma oscillations were amplified, or abolished, after optogenetic activation or selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
169
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(194 citation statements)
references
References 48 publications
25
169
0
Order By: Relevance
“…In addition, this hypothesis agrees with the prominent recruitment of neurons within the OT upon odor presentation (Carlson et al 2013;Payton et al 2012;Rampin et al 2012). Among the spectral bands that have received the most attention in terms of being shaped by odor and odor quality, are beta and gamma (Cenier et al 2008;Lepousez and Lledo 2013;Lowry and Kay 2007;Martin et al 2006Martin et al , 2007. We found that the OT is also characterized by considerable beta-band power and detectable, yet minor, gamma-band power.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, this hypothesis agrees with the prominent recruitment of neurons within the OT upon odor presentation (Carlson et al 2013;Payton et al 2012;Rampin et al 2012). Among the spectral bands that have received the most attention in terms of being shaped by odor and odor quality, are beta and gamma (Cenier et al 2008;Lepousez and Lledo 2013;Lowry and Kay 2007;Martin et al 2006Martin et al , 2007. We found that the OT is also characterized by considerable beta-band power and detectable, yet minor, gamma-band power.…”
Section: Discussionmentioning
confidence: 74%
“…If an SP cell responds with only 1–2 spikes for each round of input, it is more likely to respond faithfully to subsequent inputs. Such coupling may be important for maintaining any temporal coding feature present in beta/gamma oscillations (Laurent et al, 2001; Schaefer et al, 2006; Lepousez and Lledo, 2013) or for allowing the cortex to engage in its own oscillations (Freeman, 1959) that are coherent with those in the bulb (Bressler, 1984; Neville and Haberly, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Would silencing specific GABAergic cells disrupt odor-evoked cortical oscillations that may be driven by oscillatory bulbar inputs? Also, what impact would disrupting these detection mechanisms have on odor discrimination, which is significantly impacted by fast bulbar oscillations (Lepousez and Lledo, 2013)?…”
Section: Discussionmentioning
confidence: 99%
“…OB gamma oscillations are produced by interactions between mitral/tufted cells and granule cells. A recent study using pharmacological manipulation of GABA A receptors specifically eliminated OB gamma oscillations and demonstrated that gamma oscillations are required for odor discriminations in vivo [127]. Gamma oscillations coupling across brain areas are important for odor information transfer and learning process [128].…”
Section: Theta and Gamma Oscillationsmentioning
confidence: 99%